The Procurement of Government Goods and Services in Indonesia - Endang Asliana (Politeknik Negeri Lampung, 2012)
The procurement of government goods and services is a part that is mostly affected by corruption, collusion, and nepotism. It can be seen from many government projects that do not meet deadlines, are not well-targeted, are not of good-quality, and are inefficient. A lot of equipment is purchased but not used; buildings are damaged; the lifespans of highways and bridges are short because the technical specifications are lower or are not in accordance with specified provisions so that the lifespans of the government projects reach only 30-40%. Procurement auction that is closed or is not transparent and is not announced to public is one of the causes of high corruption in procurement of government goods and services. In Indonesia, procurement of goods and services is regulated by Presidential Decree No. 54 Year 2010, with the principles of efficiency, effectiveness, transparency, openness, competitiveness, fairness or non-discrimination, accountability. E-procurement then becomes a substitute for a closed auction. The auction can be accessed online through the Internet. The system is expected to increase openness, transparency, and accountability in central, provincial, and regency or city government agencies, and BUMN, BUMD, BHMN, and public service agencies. Keywords: public sector accounting, procurement of government goods and services, e-procurment